(untitled) (Eurasian Research Bulletin, 2022)
In this article, the ISO/IEC 27001 and ISO 9001 standards are analyzed. Based on the similarities and differences between the quality management system and the information security management system, the possibility of their integration is shown, as well as the advantages of this solution. The advantages and disadvantages of these management systems, statistics on the number of certificates issued in the world according to the relevant standards and trends in their distribution are considered in detail. It is concluded that it is possible and necessary to integrate these control systems.